How the Asian and European Communities Accept Negative Numbers - Maryati, Tita Khalis; Aisah, K; Miftah, Ramdani (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractThis research is based on several inquiries from mathematics educators on the origins of negative numbers and their acceptance in the community. This study used library research, or more precisely, bibliographical studies, as a method. The research examined how the Asian and European communities accept negative numbers. The study's findings indicated that the Asian and European communities accept negative numbers differently. In comparison to the Asian population, the European populace takes a long time to accept negative figures. It resulted in numerous contrasts between the Asian and European Communities, one of which is in terms of religiosity. This study established that religiosity has an effect on the Asian and European communities' acceptance of negative numbers.AbstrakPenelitian ini didasarkan pada beberapa pertanyaan dari pendidik matematika tentang asal-usul bilangan negatif dan penerimaannya di masyarakat. Penelitian ini menggunakan metode penelitian kepustakaan atau lebih tepatnya studi kepustakaan. Penelitian tersebut mengkaji bagaimana masyarakat Asia dan Eropa menerima angka negatif. Temuan studi menunjukkan bahwa komunitas Asia dan Eropa menerima angka negatif secara berbeda. Dibandingkan dengan penduduk Asia, penduduk Eropa membutuhkan waktu lama untuk menerima angka negatif. Hal ini mengakibatkan banyak perbedaan antara Komunitas Asia dan Eropa, salah satunya dalam hal religiositas. Studi ini menetapkan bahwa religiusitas berpengaruh pada penerimaan masyarakat Asia dan Eropa terhadap angka negatif. How to Cite: Maryati, T. K., Aisah, K., Miftah, R. (2021). How the Asian and European Communities Accept Negative Numbers. TARBIYA: Journal of Education in Muslim Society, 8(2), 167-178. doi:10.15408/tjems.v8i2.25042.